[Harmon Bennett Toone, Dairy and Poultry Science Department Head, and unidentified student] (1977)
Office photo of Harmon Bennett Toone, Dairy and Poultry Science Department Head, and unidentified student, circa December 1977. Toone was an instructor at Cal Poly from 1952 to 1977 and head of the department from 1957 until his retirement in 1977.